Perbandingan Kinerja Pegawai Sebelum dan Sesudah Penerapan e-Government (Studi pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Tanggamus) - Reza Handika; Yulianto Yulianto; Suripto Suripto (P3M STISIPOL Dharma Wacana Metro, 2018)
Performance of public sector employees as long as it is considered still low. Egovernment become one step in improving the performance of employees. This research aims to differentiate and analyze the performance of an employee before and after the implementation of e-government in Tanggamus Regency BPKAD. This research is explanatory with the quantitative approach method. Engineering data collection using the questionnaire, with 36 people samples taken from a population of 57 BPKAD employees Tanggamus Regency. Sampling techniques using Incidental with Slovin formula. The data were analyzed using the discriminant Analysis Method. Results of research are tested by a method using the variable performance of 3 employees. Indicates that there are significant differences in the variable quantity and timeliness of work before and after the implementation of the e-gov, while in variable quality of work does not indicate the existence of significant differences. The third variable is obtained from th performance of the employee before and after the implementation of the e-gov using Lambda Wilk's with the value significance . 0.000 Î± value 0.05< such shows that there has been a noticeable difference (significant) between the performance of the employee before the application of e-government performance with employees after the application of e-gov in BPKAD Tanggamus Regency. E-government has a real influence in terms of performance improvement officer. The application of e-gov is able to significantly increase the quantity of work and the timeliness, although in terms of the quality of work has not appeared a significant difference, in fully applying the e-government has brought real change in improvement the performance of employees. Keywords: E-Government, The Performance Of Employees.